Functional and environmental determinants of bark thickness in fire‐free temperate rain forest communities. Issue 10 (5th October 2015) - Richardson, Sarah J.; Laughlin, Daniel C.; Lawes, Michael J.; Holdaway, Robert J.; Wilmshurst, Janet M.; Wright, Monique; Curran, Timothy J.; Bellingham, Peter J.; McGlone, Matt S.
Abstract : PREMISE OF THE STUDY: In fire‐prone ecosystems, variation in bark thickness among species and communities has been explained by fire frequency; thick bark is necessary to protect cambium from lethal temperatures. Elsewhere this investment is deemed unnecessary, and thin bark is thought to prevail. However, in rain forest ecosystems where fire is rare, bark thickness varies widely among species and communities, and the causes of this variation remain enigmatic. We tested for functional explanations of bark thickness variation in temperate rain forest species and communities. METHODS: We measured bark thickness in 82 tree species throughout New Zealand temperate rain forests that historically have experienced little fire and applied two complementary analyses. First, we examined correlations between bark traits and leaf habit, and leaf and stem traits. Second, we calculated community‐weighted mean (CWM) bark thickness for 272 plots distributed throughout New Zealand to identify the environments in which thicker‐barked communities occur. KEY RESULTS: Conifers had higher size‐independent bark thickness than evergreen angiosperms. Species with thicker bark or higher bark allocation coefficients were not associated with "slow economic" plant traits. Across 272 forest plots, communities with thicker bark occurred on infertile soils, and communities with thicker bark and higher bark allocation coefficients occurred in cooler, drier climates. CONCLUSIONS: In non‐fire‐prone temperate rain forest ecosystems, investment in bark is driven by soil resources, cool minimum temperatures, and seasonal moisture stress. The role of these factors in fire‐prone ecosystems warrants testing.